2018
DOI: 10.4335/16.2.337-359(2018)
|View full text |Cite
|
Sign up to set email alerts
|

Vienna Construction Projects: Redirection of Project Management Critical Success Factors—More Focus on Stakeholders and Soft Skills Development

Abstract: A society, which applies frequently projects and programmes, and which provides project management-related education, research and marketing services, can be perceived as a project-oriented society (POS). More projects and programmes are performed in industry but also in new social areas, such as (small) municipalities, associations, schools and even families. "Management by Projects" becomes a macro-economic strategy of the society, to cope with complexity and dynamics and to ensure quality of the project res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…However, literature shows that soft competencies play an essential role in research project management [69][70][71][72][73][74][75][76], and PRs in the academic context need managerial skills [35,43,53]. In academic research management, leadership skills and self-efficacy are shown to be crucial: Leadership weaknesses are listed among the main problems in research project implementation and prevent projects from achieving success [43,53,77].…”
Section: The Role Of Soft Skills In Randd Project Managementmentioning
confidence: 99%
“…However, literature shows that soft competencies play an essential role in research project management [69][70][71][72][73][74][75][76], and PRs in the academic context need managerial skills [35,43,53]. In academic research management, leadership skills and self-efficacy are shown to be crucial: Leadership weaknesses are listed among the main problems in research project implementation and prevent projects from achieving success [43,53,77].…”
Section: The Role Of Soft Skills In Randd Project Managementmentioning
confidence: 99%
“…En contraste, cuando los gestores de proyectos perciben las bondades de la participación de los interesados, llegan a sopesar la cooperación de los interesados como uno de los elementos más importantes para una mejor administración del entorno en los proyectos (Wanivenhaus et al, 2018). Como resultado de la participación, se consideran las prioridades, deseos y necesidades de los interesados para atender sus necesidades más urgentes (van Holstein, 2018).…”
Section: Antecedentesunclassified